Problem of children of incarcerated parents and their position in social welfare - Đorđević Violeta; Hrnčić Jasna (Temida, 2023)
Children of incarcerated parents (CIP) face numerous challenges in realizing their rights, which have been largely overlooked in our scientific and professional community, starting from their statistical tracking. This study aims to present the research results related to the characteristics and problems of CIP and their position within the social welfare system. A mixed, descriptive and transfer design research was conducted. Data was collected through questionnaires, interviews, and file analysis. The sample included twelve children of incarcerated parents, seven of their parents (who are not incarcerated), guardians or foster parents, and 16 professionals from the Center for Social Work (CSW) in Leskovac. It was found that children of incarcerated parents have behavioural and social relationship problems. The experiences of visitation with incarcerated parents are stressful for these children. The majority of their guardians have a negative attitude towards visitation with incarcerated parents. CSW professionals do not implement measures and services specifically tailored to the problem of these children because they are lacking in the welfare system. It is necessary to develop and implement such measures in collaboration with the criminal justice system.